Assessment of Genetic Diversity for Yield and Grain Quality Traits among Heat Tolerant Germplasm Accessions of Rice (Oryza sativa L.) - Patel, T. S.; Sahu, P. K.; Mandal, Swati (International Journal of Economic Plants, 2025)
The present experiment was conducted during summer, 2013 (February–May) and kharif, 2013 (June–October) at research cum instructional farm, Department of Genetics and Plant Breeding, Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.) to evaluate yield attributing and grain quality traits among 33 heat tolerant rice germplasm lines including three standard checks (Mahamaya, Karma-Mahsuri and Indira Sona). Based on the result experimental material were grouped into 5 clusters each for both grain yield and grain quality traits. Cluster I (11) carried highest number of genotypes for grain yield. For grain quality traits cluster II (13) was notified to retain highest accession numbers. The highest inter-cluster distance was observed between cluster V and cluster III for yield traits (8.351) as well as grain quality traits (7.675) indicating the presence of wide genetic diversity among accessions to be used in hybridization programme for improving grain quality traits and maximize yield. The highest cluster mean value was observed for total spikelet plant-1 (256.7) and hulling % (81.54) might offer for direct selection of plants for higher yield and better grain quality traits. Cluster III and cluster IV group members were recognized as the most important individuals as they possessed highest cluster mean for several agronomic as well as grain quality traits such as productive tiller plant-1, 100 seed wt., harvest index, spikelet fertility%, biological yield, kernel length, hulling%, milling%, head rice recovery (HRR) and amylose content. These individuals would be used in future breeding programme to transmit genes of quality seeds into off-springs.